From Fidelity to Flexibility: Developing the Adaptive Fidelity Framework (AFF) for Pedagogical Innovations in Teacher Education - Maria Leah Paola Estacio; Ronald Quileste; Kathleen Morales (Universitas Cokroaminoto Palopo, 2025)
This mixed-methods study explored the implementation of the Dynamic Learning Program (DLP), a student-centered pedagogy, in a Philippine private school, examining adherence, achievement, and stakeholder experiences. Through surveys, standardized tests, and interviews, the research revealed robust adherence but variable achievement, with stronger outcomes in literacy than STEM. Teachers’ adaptations, such as supplemental explanations, addressed conceptual challenges, highlighting the need for flexibility. These findings informed the Adaptive Fidelity Framework (AFF), a novel model balancing fidelity to core principles, teacher-led adaptation, and contextual moderators like resources and student readiness. The AFF redefines implementation science by prioritizing dynamic, context-responsive fidelity, offering a scalable approach for teacher education and policy in low- and middle-income countries and beyond. The study underscores the importance of teacher agency in navigating fidelity-adaptation tensions, contributing to global discourses on equitable, sustainable reform. Implications include training teachers as adaptive implementers and designing monitoring systems that value contextual responsiveness. This Philippine case provides a blueprint for scaling innovations worldwide, advancing efforts to balance educational quality with equity.